The Importance of Digital Marketing Integration in Strategic Management Planning - Saputra, Argian (Ridwan Institute, 2024)
This study discusses the importance of digital marketing integration in the company's strategic management plan. Digital marketing has become a key factor in achieving business goals in the increasingly interconnected digital era. The formulated problems include understanding of digital marketing and its integration benefits, challenges in adopting digital marketing, and the role of technology and data analysis in supporting digital marketing integration and accurately measuring campaign effectiveness. In the context of understanding digital marketing, this research outlines the definition and role of digital marketing in the overall marketing strategy. Digital marketing integration opens opportunities to target markets more precisely, enhance customer engagement, and optimize customer experiences. Challenges include technical constraints, changes in organizational culture, and a lack of understanding of digital technology. To overcome these challenges, companies need to invest in resources, gain support from top management levels, and prioritize a data-driven approach in decision-making. The role of technology and data analysis is pivotal in supporting digital marketing integration. Companies should leverage data analytics technology and marketing automation to understand customer behavior, identify market trends, and deliver relevant messages automatically. Data analysis also aids in measuring campaign performance and calculating ROI, enabling companies to allocate marketing budgets effectively. In conclusion, digital marketing integration is not just a choice but a necessity for companies to remain relevant and competitive in an increasingly digital business era. By confronting challenges and optimizing the role of technology, companies can achieve competitive advantage, enhance marketing efficiency, and attain long-term success. A data-driven approach and the utilization of data analysis technology will be key for companies to achieve desired business goals.